Sperm Mitochondria, the Driving Force Behind Human Spermatozoa Activities: Its Functions and Dysfunctions - A Narrative Review - Kumar, Naina (Current Molecular Medicine, 2023)
Male infertility is a major issue, and numerous factors contribute to it. One of the important organelles involved in the functioning of human spermatozoa is mitochondria. There are 50-75 mitochondria helically arranged in mid-piece bearing one mitochondrial DNA each. Sperm mitochondria play a crucial role in sperm functions, including the energy production required for sperm motility and the production of reactive oxygen species, which in the physiological range helps in sperm maturation, capacitation, and acrosome reaction. It also plays a role in calcium signaling cascades, intrinsic apoptosis, and sperm hyperactivation. Any structural or functional dysfunction of sperm mitochondria results in increased production of reactive oxygen species and, a state of oxidative stress, decreased energy production, all leading to sperm DNA damage, impaired sperm motility and semen parameters, and reduced male fertility. Furthermore, human sperm mitochondrial DNA mutations can result in impaired sperm motility and parameters leading to male infertility. Numerous types of point mutations, deletions, and missense mutations have been identified in mtDNA that are linked with male infertility. Methods: Recent literature was searched from English language peer-reviewed journals from databases including PubMed, Scopus, EMBASE, Scholar, and Web of Science till September 2021. Search terms used were “Sperm mitochondria and male fertility”, “Bioenergetics of sperm”, “Sperm mitochondria and reactive oxygen species”, “Sperm mitochondrial mutations and infertility”. Conclusion: Sperm mitochondria is an important organelle involved in various functions of human spermatozoa and sperm mitochondrial DNA has emerged as one of the potent biomarkers of sperm quality and male fertility.
Keywords: Spermatozoa